Tonal Dissonance Curves - Garrigan, Kaisey; Germain, Adam; Abu Eid, Hitham (My University, 2013)
The purpose of this study was to utilize Fourier analysis techniques and software MATLAB and FAWAVE, using the human voice as the instrument, to adapt the work of Dr. William A. Sethares on tonal dissonance curves. Dr. Sethares' research analyzes the relationship between sensory dissonance for two tones, and their frequency intervals with musical instruments.
Color poster with text, images, charts, and graphs.
Keywords: Music; Frequency; Harmonic amplitudes; Dissonance; Posters